O papel dos recursos humanos na inclusão da pessoa com deficiência (PCD) - SOUSA, Júlia Helena Moraes de (109, 2023)
Atualmente, no Brasil, várias discussões têm se levantado a respeito da inclusão das pessoas com deficiência (PcDs), assim como leis têm sido feitas no sentido de proteger os direitos de cidadãos que até então eram considerados à margem da sociedade. Nesse contexto, esta pesquisa aborda os problemas enfrentados por essas pessoas para serem inseridas no mercado e trabalho e seu objetivo é discutir a importância do profissional de Recursos Humanos (RH) nesse processo. A pesquisa, de cunho qualitativo, realizou-se de forma bibliográfica, em artigos e leis. Identificouse que o profissional de RH é o responsável pela aplicação da Lei de Cotas Nº 8.213, de 24 de julho de 1991, e reconhecimento da oferta de emprego para Pessoas com Deficiência (PCD) como um direito. Bem como fica encarregado de perceber a PcD além de sua deficiência, detectando suas competências, treinando, cuidando para que o ambiente físico e social esteja acessível e corretamente adaptado, para que a pessoa com deficiência tenha pleno desenvolvimento, condizendo com suas necessidades e assim contribuindo com a organização rumo ao seu objetivo, sem ser prejudicada perante os demais colaboradores. O gestor pode mudar a cultura do estigma de que o deficiente “produz menos”, expondo que a inclusão é um ato de responsabilidade e equidade social, combatendo formas de preconceito da cultura organizacional, além disso a diversidade é um fator importante para criatividade.

This article addresses the challenges encountered by individuals with disabilities in their efforts to be integrated into society. Currently, in Brazil, there are ongoing discussions about the inclusion of people with disabilities (PwDs), accompanied by the enactment of laws designed to safeguard the rights of individuals who were previously marginalized. Within this context, this research specifically focuses on the hurdles faced by PwDs when seeking employment, aiming to underscore the pivotal role of Human Resources (HR) professionals in this process.This qualitative research relies on a bibliographic approach, encompassing articles and laws. It reveals that HR professionals play a crucial role in the implementation of Quota Law No. 8,213, dated July 24, 1991, ensuring that employment opportunities for People with Disabilities (PWD) are recognized as a fundamental right. Their responsibilities extend to perceiving PwDs beyond their disabilities, identifying their skills, facilitating training, and guaranteeing that the physical and social environment is accessible and appropriately adapted. This comprehensive approach is aimed at enabling individuals with disabilities to achieve full development, aligning with their specific needs. Simultaneously, HR professionals contribute to organizational objectives without compromising the well-being of other employees.By assuming a proactive stance, managers can transform the prevalent notion that individuals with disabilities are less productive. They can emphasize that inclusion is an act of responsibility and social equity, challenging prejudicial attitudes within the organizational culture. Furthermore, the recognition of diversity emerges as a vital catalyst for fostering creativity
The role of human resources in the inclusion of people with disabilities (PWD)
Keywords: Competência administrativa; Direito administrativo; Inclusão social; Preconceito racial; Gestão e Negócios